2014
DOI: 10.1007/978-3-319-07491-7_27
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of DCT-Based Denoising Techniques Applied to Texture Images

Abstract: Textures or high-detailed structures contain information that can be exploited in pattern recognition and classification. If an acquired image is noisy, noise removal becomes an operation to improve image quality before further stages of processing. Among possible variants of denoising, we consider filters based on orthogonal transforms, in particular, on discrete cosine transform (DCT) known to be able to effectively remove additive white Gaussian noise (AWGN). Besides, we study a representative of nonlocal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…Meanwhile, there are recently proposed approaches to prediction [15,[18][19][20][21] that are fast and based on another principle. It is supposed that there exists a rather strict dependence between one or several "input" parameters (that can be easily calculated for an analyzed image) and a parameter that characterizes denoising efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, there are recently proposed approaches to prediction [15,[18][19][20][21] that are fast and based on another principle. It is supposed that there exists a rather strict dependence between one or several "input" parameters (that can be easily calculated for an analyzed image) and a parameter that characterizes denoising efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some steps towards designing prediction procedures have been done [15,[17][18][19][20][21]. In [17], it has been shown that for non-local denoising methods applied to remove additive white Gaussian noise (AWGN) it is possible to predict potential output mean square error (MSE) without having the corresponding reference image.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a task is to remove this noise preserving the texture features in a maximally careful manner. 17,32,35,36,46,54 One might expect that this task of e±cient texture denoising which was already relevant a decade or two ago, 17,32,46 and now with all recent advancements (nonlocal ltering methods) in image denoising 11,12,14,26,46 has been successfully solved. However, this is not true.…”
Section: Introductionmentioning
confidence: 99%
“…27 It has been shown in Refs. 35 and 36 that the problems in noise removal arise for¯lters based on discrete cosine transform (DCT) 16,22,26 and one of the most advanced nonlocal¯l-tering methods, BM3D (block matching three dimensional)¯lter. 11 Then, one might think that denoising techniques based on other principles are able to cope with a noise in texture images in a better way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation